Trend analysis of monthly rainfall data using the Innovative Polygon Trend Analysis (IPTA) in the Tafna Watershed (Northwestern Algeria) - Fettam, Djillali; Gherissi, Radia; Otmane, Abdelkader (Italian Journal of Agrometeorology, 2025)
Trend analysis of hydroclimatic data is essential for assessing climate variability. Precipitation is an important parameter affected by climate change in the Mediterranean climate, particularly in sensitive regions like the Tafna watershed in Northwestern Algeria. This study used the Innovate Polygon Trend Analysis (IPTA) to study the change between two successive months. Additionally, the Mann-Kendall (MK) test was compared to the IPTA method in detecting trends. Total monthly rainfall data was collected from 14 stations in the Tafna watershed over 50 years from the hydrological year 1970-71 to 2019-20. The maximum trend length using the IPTA method was found in the transition May-June for most stations. The MK test does not indicate any significant trend (increase and decrease) in most of the months at all stations. In contrast, the IPTA method shows an increasing trend in October and January in all stations; August, September, November, and December show an increasing trend in most stations. A decreasing trend was found in February and March at all stations and in May at most stations. The results showed that the MK test detected a significant trend in 6.5% of the total months analyzed in this study, whereas the IPTA method identified a trend in 88.7% of the total months. The findings revealed that the IPTA method was more sensitive to detecting trends in precipitation data than the MK test, which suggests the IPTA method could be a valuable tool for assessing trends of precipitations in the Tafna watershed.